Exchange stiffness and damping constants in diluted CoxFeyB1−x−y thin films. (20th September 2017) - Belmeguenai, M; Apalkov, D; Roussigné, Y; Chérif, M; Stashkevich, A; Feng, G; Tang, X
Abstract: The magnetic properties of 20 nm thick sputtered CoFeB thin films of different compositions have been investigated and compared to those of traditional 3D ferromagnetic materials (Co, Fe and Ni). A vibrating sample magnetometer has been used to measure their magnetization at saturation ( M s ). Their dynamic magnetic properties were studied using microstrip line ferromagnetic resonances, as well as Brillouin light scattering (BLS) techniques. The effective magnetizations and gyromagnetic factors are firstly measured from resonance spectra obtained for in-plane and perpendicular applied fields. The angular dependence of the resonance field then allows us to derive parameters describing the in-plane magnetic anisotropy, which is found to result from a superposition of small uniaxial and fourfold terms. Frequency and angular dependencies of the ferromagnetic resonance linewidth have been used to determine the Gilbert damping coefficient for each sample. The perpendicular surface standing modes, observed in BLS spectra, allow the evaluation of the exchange stiffness constant, which is found to vary linearly with M s (for CoFeB), in agreement with the simple model presented here. Finally, the thickness dependence of the Gilbert damping parameter of Co15 Fe45 B40 revealed a contribution due to spin pumping leading to a spin mixing conductance of 31 nm −2 . The BLS measurements on the 5 nm thick Co15 Fe45 B40 film evidenced a large frequency asymmetry attributed to the interfacial Dzyaloshinskii–Moriya interaction (DMI) originating from the interface with Pt. The surface DMI constant has been estimated to be = −0.33 pJ m −1 .